On curves with constant curvatures - Ebbens, Matthijs (Student Undergraduate Research E-journal!, 2015)
One of the fields of research of Computer Aided Geometric Design is approximating complex curves by simpler curves. Curves with constant curvatures are useful tools for these purposes. However, parametrizations of such curves are not always easily given. In this paper we will derive several necessary and sufficient geometric conditions for a curve to have constant curvatures, both in Euclidean geometry and in affine geometry.